Klinik Penyusunan Instrumen Penelitian Guna Peningkatan Kualitas Skripsi Mahasiswa - Hasnawati Hasnawati; Khairun Nisa; Setiani Novitasari; Hikmah Ramdhani Putri (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The quality of a student's thesis is highly dependent on the accuracy and appropriateness of the research instruments used. However, many final year students still experience difficulties in designing instruments that meet the requirements of validity, reliability, and suitability for research objectives, resulting in delays in completion and a decline in the quality of scientific work. This community service activity aims to provide practical assistance through the "Research Instrument Development Clinic" to improve student competency in developing standardized instruments. The implementation method includes preparation, delivery of materials and assistance in developing instruments, as well as evaluation in the form of pretests and posttests and satisfaction questionnaires. This community service activity was carried out in room F17, campus 2, FKIP, University of Mataram on Saturday, August 23, 2025. The results of the activity showed a significant increase in the understanding and technical skills of the participants. A total of 12 participants successfully produced drafts of instruments that had been validated in terms of content. The level of participant satisfaction reached 85%, with the majority stating that this clinic was very helpful in accelerating and improving the quality of the thesis preparation process. The conclusion of this activity is that the research instrument mentoring clinic model has proven effective as a strategy to improve the quality of student theses through a practical, collaborative, and sustainable approach. It is recommended that similar activities be routinely integrated into campus academic mentoring programs and expanded in scope.